KONSEP DAN STRATEGI DAKWAH ISLAM DI INDONESIA - Nur Khoiriyah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2015)
Religious fundamentalism movement in Indonesia is not just a discourse. There have been many groups doing hard movement in the name of defense against God. Da'wah-propaganda marathon done, even with violence. The question then is, whether they forgot that was in a heterogeneous country ?. The country's independence by struggle together all religions, classes and races. And so also should all components of this country fought for ideals together is prosperous. Understanding the historical context of the rise of fundamentalist movements is very important to understand the flow of thought. With this understanding then pull back on the Indonesian context. How good considering the missionary movement in Indonesian Islam is the majority religion. With a wide range of variants and Islamic da'wah approach provides the option to choose anyone. In this paper begins a discussion of religious fundamentalist movements. This understanding is then drawn on a typical Islamic thought and friendly in accordance with the conditions in Indonesia. With this understanding starategi propaganda accordance with pemerima propaganda that Indonesian society can be formulated.